2010
DOI: 10.5001/omj.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Presentation and Survival of Breast Cancer in a Teaching Hospital in North Western Nigeria

Abstract: The overall survival rate was low and patients with early breast cancer had better survival than those with advanced disease. Majority of the patients were young premenopausal women with advanced breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
45
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 13 publications
17
45
4
Order By: Relevance
“…Our finding is in agreement with the study carried in Zaria [32]). The reason for this observation may be due to the fact that the Hausa and Fulani are the major ethnic groups in Sokoto, North Western Nigeria.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding is in agreement with the study carried in Zaria [32]). The reason for this observation may be due to the fact that the Hausa and Fulani are the major ethnic groups in Sokoto, North Western Nigeria.…”
Section: Discussionsupporting
confidence: 94%
“…Our finding is in agreement with the study carried out in Zaria [32] which indicated that half of their breast cancer patients presented with stage 3 diseases.…”
Section: Discussionsupporting
confidence: 93%
“…10 The incidence of malignant growth amongst the breast lesions is fairly common with more number of cases being detected in recent years and so it warrants the need for detecting out the morbid pattern of the tumour. Breast cancer kills 376000 women a year worldwide and there are about 900000 new case annually with increasing incidence in most parts of the world and especially developing country where it is almost as common as cervical cancer, the leading female cancer in developing world.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a retrospective study was performed at Ahmadu Bello University Teaching Hospital in Nigeria, a country in which approximately 49% of the population is younger than 15 years of age 12 . In this study, the average age of participants with breast cancer was 44.5 years, the majority (57.4%) was between 30 and 49 years of age, and 62% of the women were premenopausal 13 . Ghiasvand, et al 14 carried out a hospital-based case-control study that included 521 women with histologically confirmed breast cancer and 521 controls matched by age and place of residence.…”
Section: Risk Factorsmentioning
confidence: 99%